Quantitative Evaluation of Clinical Outcomes of Levonorgestrel-Releasing IUCD (LNG-IUS) in Heavy Menstrual Bleeding: a Comparative Study - Venu gopal; Aidarbek kyzy Aidabbek; koushik reddy; eepriya; rambalan; vikrananth (InterConf. Scientific Collection, 2026)
One of the widespread diseases affecting the reproductive system in women is heavy menstrual bleeding, causing many complications such as iron deficiency anemia and fatigue, and lowering the quality of life of women significantly. In this paper, the efficacy of hormonal intrauterine contraception is evaluated in order to meet the demand for efficient treatment methods that have long-lasting effects without surgeries. The purpose of the current work is to perform a quantitative analysis of the clinical effectiveness in terms of decrease in menstrual blood loss, improvement in blood indicators, pain relief, menstruation disappearance, and patients’ satisfaction. It is necessary to analyze the results of randomized clinical trials, prospective cohorts, and systematic reviews on the subject matter. The obtained data suggest the presence of a significant decrease in menstrual blood loss, improvement in hemoglobin level, and pain symptoms. Many patients stopped having menses while using the new method. It proved to be more efficient, satisfactory, and easier to continue compared to conventional therapies. Thus, this article offers a unique analysis combining quantitative measures and comparative evaluation of the effect of the therapy on patients’ health.